A super stretchable and sensitive strain sensor based on a carbon nanocoil network fabricated by a simple peeling-off approach. Issue 42 (23rd October 2017) - Deng, Chenghao; Pan, Lujun; Zhang, Dongmei; Li, Chengwei; Nasir, Habib
Abstract : Through a simple peeling-off approach, a super stretchable and sensitive strain sensor based on a carbon nanocoil network is fabricated. Abstract : Despite the tremendous progress in wearable and smart strain sensors, it is still a challenge to develop a highly sensitive, stretchable, and low-cost sensor. Herein, a super stretchable and sensitive strain sensor fabricated by a simple peeling-off approach is reported. The strain sensor is prepared by peeling off a thin as-grown carbon nanocoil (CNC) film from a substrate using a stretchable polydimethylsiloxane (PDMS) film or a flexible adhesive tape. Herein, we took advantage of the spring-like morphology and the original network of the CNCs. The sensor is used to detect pressure, tension, and bend. The strain range and maximum real-time gauge factor reach 260% and 190, respectively, with a rapid response time (less than 12 ms). The contrary resistance responses under tension and bend make it possible to distinguish the direction and type of strain. The sensor is used to monitor a strain over a wide range, from human pulse to the impact of a 0.9 kg weight. The high sensitivity and stretchability, easy and cheap fabrication, and effective interaction with human motions suggest the great potential applications of this sensor in wearable strain sensors and smart systems.